ТАЙШИРЫН УСАН ЦАХИЛГААН СТАНЦТАЙ ХОСЛОН АЖИЛЛАХ НАРНЫ ЦАХИЛГААН СТАНЦЫН СУДАЛГАА - Чадраа, Баатар; Гантөмөр, Г; Сайнболд, С; Баасандорж, Ч; Мэндбаяр, Б; Пүрэвдалай, Э (Proceedings of the Mongolian Academy of Sciences, 2016)
This paper presents study and results of 10 MW Solar PV plant that will be work with Taishir hydropower plant (as a hybrid system) in Mongolian West region.